Crosshairs - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller, 2024)
NYC detective Michael Bennett teams up with a former Army Ranger and sniper whose long, unexplained absences from duty causes suspicions during the investigation of a serial killer.